PENGARUH PENGGUNAAN BOX POWER IGNITION TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR KARBURATOR - Hengky Prasetyo Wibowo; Taufik Wisnu Saputra; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
This study aims to determine the influence of voltage variations in box power ignition on the fuel consumption of a 2011 Honda Supra X 125 motorcycle. One way is to use box power ignition. The research method used is experimental. This research data was obtained using samples of Honda Supra X 125 motorcycle in 2011. The independent variable is the use of box power ignition with voltage variations of 14.4 V to 15.9 V. The dependent variable fuel consumption measured through stationary and road tests on predetermined routes. The maximum fuel consumption in stationary tests was obtained at a voltage variation of 14.7 V, measuring 2.54 ml/minute, a decrease of 0.98 ml/minute. The average fuel consumption increase was 3.55 ml/min. The maximum fuel consumption in road tests was obtained at a voltage variation of 15.3 V, measuring 28.13 m/ml, an increase of 11.46 m/ml. The average fuel consumptionincrease was 22.92 m/ml from the standard condition.